Experiments Toward Hyper-Local Reverse Heat Flow Assemblies. Issue 2 (3rd July 2018) - Junghans, Lars; Tish, Daniel; Brugmann, Dustin; Velikov, Kathy; Thün, Geoffrey
Abstract : Latitudo Borealis is a project that develops an innovative cold-climate wall assembly that combines new passive opaque building envelope technologies to absorb, store, and transfer solar energy into a building during winter, with exterior shading to mitigate overheating during summer. The research encompasses three domains of architectural research: the physical testing and optimization of high-performance envelope assemblies, the use of computational evolutionary algorithms in the design of highly tuned climate-informed shading configurations, and new tools and processes for precise robotic heat bending of wood. It is demonstrated that the assemblies are capable of successfully absorbing and redirecting heat into the building interior in winter to improve building performance. The application of the experimental envelope assembly is further explored through the design of an unbuilt test case pavilion.